Franchising strategies : the entrepreneur's guide to success - Teixeira, Ed; Chan, Richard, (Professor of Business) (New York : Routledge, 2023)
"A comprehensive and accessible companion to a proven business model, this book shows how to franchise an existing business, supported by case studies, data, and research reports on the franchise industry. For small to medium sized businesses, franchising can lead to successful and profitable growth, and plays an important role within the US economy. Utilizing a proprietary dataset with the most up-to-date statistics regarding a range of franchising trends, this analytical guide is based on management research frameworks that will lead to better understanding of a range of franchising strategies. Issues covered include: The franchising business model, including its history, economic impact, and regulations. Critical factors that significantly influence franchising success, enabling a comprehensive feasibility analysis of franchising potential or existing business ideas. Implementation components of franchising strategies, such as different franchise structures, regional development plans, and future trends With its clear focus and practical orientation, this book will be a valuable resource for entrepreneurs, as well as undergraduate and postgraduate students, interested in acquiring the knowledge, skills, and abilities to succeed in franchise"--
Includes bibliographical references and index.
Keywords: Franchises (Retail trade); Small business -- Management; Strategic planning